Descriptive Analysis of Science Process Skills (SPS) and Scientific Reasoning (SR) of High School Students and Pre-service Teacher in Science Learning - Zaini, Muhammad; Ramdani, Agus; Harjono, Ahmad; Makhrus, Muhammad; Doyan, Aris; Sukarso, A.A (Universitas Islam Negeri (UIN) Mataram, 2025)
This study aimed to analyze science process skills (SPS) and scientific reasoning (SR) among high school students and prospective teachers. This study used a quantitative descriptive approach with a survey method involving a self-report perception questionnaire to collect data from eleventh and twelfth grade science students and 187 prospective teachers majoring in Physics Education. The results showed that Science learning in high school and pre-service teachers has begun to integrate science process skills (SPS) and scientific reasoning (SR), but its implementation is inconsistent and practicums are still less intensive, so that SPS strengthening is not optimal. Obstacles that arise include limited practicums and facilities, the dominance of theoretical learning, difficulty understanding abstract concepts, and low systematic thinking habits and confidence in scientific argumentation. On the other hand, students and pre-service teachers hope that science learning is more based on interesting and contextual practicums, relevant to everyday life, utilizing technology, and designed collaboratively and adaptively so that SPS and SR can develop simultaneously and be ready to face the challenges of the 21st century.